Comparative analysis of arabic language learning systems in malaysia and thailand - Hanan Riswar; Dailatus Syamsiah; Salwa Malaeh (At Turots: Jurnal Pendidikan Islam, 2025)
This research is motivated by the significance of Arabic language learning in Southeast Asia, particularly in Malaysia and Thailand, which possess distinct social, cultural, and educational contexts. The main problem addressed concerns how Arabic language learning systems outside the campus are implemented in both countries, the challenges encountered, and the extent to which the applied approaches enhance learning effectiveness. The purpose of this research is to analyze the similarities and differences in Arabic language learning systems in Malaysia and Thailand, as well as to identify the supporting and inhibiting factors in their implementation. This research employs a qualitative approach with a comparative case study method. Data were collected through interviews, observations, and documentation in several educational institutions, including Universiti Putra Malaysia, Universiti Malaya, Jami’ah Islam Syeikh Daud Al-Fathoni, and Tamavitya Multini School. Data analysis was conducted using the interactive model of Miles and Huberman, which involves data condensation, data display, and conclusion drawing. The findings reveal significant differences between the two countries. Malaysia emphasizes digital technology integration, research-based curricula, and strong government support in strengthening Arabic language learning. In contrast, Thailand highlights Islamic values through traditional methods such as halaqah and the study of classical texts, although it has begun to adopt digital technology as a complementary tool. The study also underscores the strategic role of non-formal educational environments in shaping students’ linguistic and religious competencies. The contribution of this research lies in mapping Arabic language learning systems outside the campus, not only at the institutional level but also in emphasizing the importance of cross-country collaboration in developing adaptive learning models that respond to global challenges while remaining rooted in local values and Islamic scholarly traditions.